Effect of discipline and work environment performance of paramedics (case study of regency hospital Arifin Achmad Pekanbaru) - Nurafni '; Machasin '; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aims to determine how the variables influence the discipline and work environments simultaneously and partially on the performance of nonnursing paramedical staff (case studies from hospitals Arifin Achmad Pekanbaru).The population is non nursing paramedic Arifin Achmad Hospital Pekanbaru , amounting to 111 people , with a total sample of 53 people . Analysis of the data used is descriptive analysis , as it also uses the quantitative analysis using multiple linear regression with SPSS version 17:00.From the results of the testing that has been done , simultaneous regression test ( F-test ) showed that the workplace environment discipline and simultaneously significant effect on the performance of non- nursing paramedics . The magnitude of the effect that the coefficient of determination ( R2 ) by the two variables simultaneously on the dependent variable while the remaining 96.00 % 4.00 % influenced by other variables not examined in this study . Partial test results (t test ) showed that Working Environment variables have the discipline and significant effect on the dependent variable performance paramedics non nursing.Keyword : Discipline, Work Environment and Performance.